Persepsi Dokter Hewan Praktisi Hewan Kecil terhadap Telemedicine di Masa Pandemi Covid-19 - Muhammad Fadly Aulia; Dwi Cipto Budinuryanto; Okta Wismandanu (Acta VETERINARIA Indonesiana, 2021)
Telemedicine is defined as remote diagnose and patient care using telecommunications technology. Recently telemedicine technology was introduced to the field of veterinary medicine. Due to the nature of telecommunications, a veterinarian will utilize telemedicine technology as a means of assessing patient severity and providing medical advice. The perception of veterinarians, especially small animal practitioners, to telemedicine is influenced by many factors, for example: age, desire (expectation), attention (focus), information obtained, and other factors. This study aims to determine the factors that influence veterinarians' perceptions of telemedicine. This research is expected to be an input in implementing telemedicine in practice. The design of this study is descriptive method, where the sampling method uses a questionnaire filled out by small animal practitioners online. The results showed that the pandemic had no impact on veterinary services. But there is an adaptation of practice procedure. Respondents are neutral towards the application of telemedicine, but the majority of respondents who have implemented telemedicine think that the application of telemedicine has a good impact on health services. There are many obstacles felt by respondents in implementing telemedicine.